Management of Acute Traumatic Spinal Cord Injury: A Review of the Literature - Wang, Timothy Y.; Park, Christine; Zhang, Hanci; Rahimpour, Shervin; Murphy, Kelly R.; Goodwin, C. Rory; Karikari, Isaac O.; Than, Khoi D.; Shaffrey, Christopher I.; Foster, Norah; Abd-El-Barr, Muhammad M. (Frontiers in Surgery, 2021)
Traumatic spinal cord injury (TSCI) is a debilitating disease that poses significant functional and economic burden on both the individual and societal levels. Prognosis is dependent on the extent of the spinal injury and the severity of neurological dysfunction. If not treated rapidly, patients with TSCI can suffer further secondary damage and experience escalating disability and complications. It is important to quickly assess the patient to identify the location and severity of injury to make a decision to pursue a surgical and/or conservative management. However, there are many conditions that factor into the management of TSCI patients, ranging from the initial presentation of the patient to long-term care for optimal recovery. Here, we provide a comprehensive review of the etiologies of spinal cord injury and the complications that may arise, and present an algorithm to aid in the management of TSCI.